Mapping of scientific production on uncertainty in international environmental basis - Silveira-Martins, Elvis; Rossetto, Carlos Ricardo (Revista de Administração da UFSM, 2018)
The purpose of this article is to map the scientific literature on the topic environmental uncertainty in international databases ProQuest and EBSCO providing results on the state of the art of this subject and the characteristics of scientific papers published. The method used was bibliometrics, being investigated 97 items from a universe of 1.194. All of the works comprised the period from 1975 to 2010. The results suggest that: a) during the period examined different social networks of researchers and institutions were formed to study this issue, b) the work of Duncan (1972), although it’s been nearly four decades of its publication, it continues to influence the formulation variables for the measurement of environmental uncertainty, and c) the research on environmental uncertainty has received over the years other terminologies and methodologies. It was observed that the studies were applied in various business segments, always aiming to minimize the environmental turbulence and thereby maximizing organizational results. This research also revealed that the way to measure them cannot be normalized, since each segment is facing a different environment several variables (customers, suppliers, competitors, society, politics, government actions, among others).